The mine drainages diffusion and physical simulation are in area of the Black sea - Biliaiev, M. M.; Kyrychenko, P. S. (Science and Transport Progress, 2011)
An experiment to model the mine waste waters discharge into the Black Sea was carried out. The experiment was held in the water channel. Some experimental results are presented.